Tactile modulation of memory and anxiety requires dentate granule cells along the dorsoventral axis - Chi Wang (Nature Portfolio, 2020)
Touch can positively modulate cognitive performance and emotional response. Here the authors demonstrate that enriched tactile experience improves memory and reduces anxiety in adult mice by remodelling the pathway from the primary somatosensory cortex to the dentate gyrus.